The Burden of Comorbidity Between Bipolar Spectrum and Obsessive-Compulsive Disorder in an Italian Community Survey - Carta, Mauro Giovanni; Fineberg, Naomi; Moro, Maria Francesca; Preti, Antonio; Romano, Ferdinando; Balestrieri, Matteo; Caraci, Filippo; Dell'Osso, Liliana; Disciascio, Guido; Drago, Filippo; Hardoy, Maria Carolina; Roncone, Rita; et al. (Frontiers in Psychiatry, 2020)
Background: The impact of the comorbidity between Obsessive-Compulsive Disorder (OCD) and Bipolar Disorder Spectrum (BDS) remains to be clarified. The objective of this study was to study: the lifetime prevalence of OCD, the strength of the association of OCD with comorbid BDS and the role of comorbidity of OCD with BDS in the impairment of health-related quality of life (HRQoL) in an Italian community survey. Methods The study is a community survey. The sample (N = 2,267; women: 55.3%) was randomly selected after stratification by sex and four age groups from the municipal records of the adult population of one urban, one suburban and at least one rural area in six Italian regions. Physicians using a semi-structured interview (Advanced Tools and Neuropsychiatric Assessment Schedule, ANTAS-SCID) made DSM-IV diagnoses of OCD, Major Depressive Disorder (MDD) and Bipolar Disorder (BD). HR-QoL was measured by the Health Survey Short Form (SF-12). Lifetime Hypomania and subthreshold hypomania were screened by the Mood Disorder Questionnaire (MDQ). BDS was defined as the sum of people positives for hypomania at MDQ with or without a mood disorder diagnosis plus people with a BD-DSMIV diagnosis even if negative at MDQ. Results Overall, 44 subjects were diagnosed with OCD, 6 with MDD and 1 with BD. The lifetime prevalence of OCD was 1.8% in men (n=18) and 2.0% in women (n=26). MDD with lifetime subthreshold hypomania (i.e., people screened positive at the MDQ, even without diagnosed mania or hypomania at the interview) was associated with OCD (OR=18.15, CI95% 2.45-103.67); MDD without subthreshold hypomania (and screened negative at the MDQ) was not (OR=2.33, CI95% 0.69-7.01). People with BDS were strongly associated with OCD (OR=10.5, CI95% 4.90-12.16,). People with OCD and BDS showed significantly poorer HR-QoL than people with OCD without BDS (F=9.492; P<0.003). Discussion The study found a strong association between BDS and OCD. BDS comorbid with OCD was associated with more severe impairment of HR-QoL than people with OCD without comorbid BDS. Identification of symptoms of hypomania, including subthreshold symptoms, may, therefore, be important in people with OCD as they might predict a course with poorer HR-QoL.